Monitoring underground construction a best practice guide (ICE, 2011)
Monitoring is a subject of particular importance to underground construction works. It is often a key risk mitigation measure both for the control of the construction process and the protection of existing assets affected by excavations.
Keywords: Underground construction.; elektronické knihy; electronic books